Efficacy of intranasal insulin in improving cognition in mild cognitive impairment or dementia: a systematic review and meta-analysis - Long, Cong; Han, Xuke; Yang, Yunjiao; Li, Tongyi; Zhou, Qian; Chen, Qiu (Frontiers in Aging Neuroscience, 2022)
Background: Insulin modulates many aspects of brain function relevant to mild cognitive impairment (MCI) or dementia, and can be delivered to the brain using intranasal(IN) devices. Intranasal insulin enhanced memory in small, single-site studies of MCI and dementia. Due to common pathophysiological findings of cognitive diseases like Alzheimer’s disease (AD) with diabetes mellitus (DM), insulin has been suggested as a possible treatment for mild cognitive impairment or dementia. A safe alternative to IV insulin is intranasal insulin. Objective: The aim of this systematic review is to investigate the efficacy of IN insulin on the cognitive function of patients with either MCI or dementia. Methods: A literature search of the electronic databases to identify RCTs investigating the effects of IN insulin administration on cognitive tasks, in patients with MCI or dementia. Sixteen studies (899 patients) met our inclusion criteria. Results: Intranasal insulin improved story recall performance of apoe4 (-) patients with MCI or dementia, Other cognitive functions were not affected, but there were some positive results in functional status and daily activity. Conclusion: Since IN insulin is a safe intervention, future studies should be conducted with larger doses and after a proper selection of patients and insulin types.